2021
DOI: 10.1155/2021/2807054
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the Factors Influencing the Behavior of Purchasing Enterprise Brand Fruits: Empirical Study Based on 312 Consumers in China

Abstract: Based on summarizing the factors that influence consumers’ purchasing of fruits and vegetables, by establishing the theoretical framework that describes the factors influencing the behavior of purchasing enterprise brand fruits, designing the questionnaire, collecting data, and analyzing the data of 312 consumers by binary logistic regression, this article finds that there are mainly 6 factors influencing the behavior of purchasing enterprise brand fruits, namely, gender, the convenience of purchase, taste, ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…Also, our results showed that consumers are willing to pay a premium for snacks with fruits and vegetables. This result was consistent with an analysis that was conducted by Fang and Levy, 52 who found that Chinese and French consumers would pay more for organic fruits. Only two of the four experiments that assessed consumer WTP for food with reduced salt or sodium showed positive results.…”
Section: Discussionsupporting
confidence: 92%
“…Also, our results showed that consumers are willing to pay a premium for snacks with fruits and vegetables. This result was consistent with an analysis that was conducted by Fang and Levy, 52 who found that Chinese and French consumers would pay more for organic fruits. Only two of the four experiments that assessed consumer WTP for food with reduced salt or sodium showed positive results.…”
Section: Discussionsupporting
confidence: 92%
“…Liu et al (2019) delve into the impact of post-purchase evaluation on electronic word-of-mouth (eWOM) giving behavior, underlining its influence on subsequent consumer actions. Jiang et al (2021) contribute to the understanding of postpurchase behavior and evaluation, showcasing the repercussions on consumer behavior. Wang et al (2019) explore the connection between in-store slack, post-purchase evaluation, and purchasing behavior, revealing intricate dynamics in the decision-making process.…”
Section: Post-purchase Evaluationmentioning
confidence: 99%